Evolutionary specialization of recoding: Frameshifting in the expression of S. cerevisiae antizyme mRNA is via an atypical antizyme shift site but is still +1 - IVANOV, IVAYLO P. (Copyright 2006 by RNA Society, 2006)
An autoregulatory translational shift to the +1 frame is required for the expression of ornithine decarboxylase antizyme from fungi to mammals. In most eukaryotes, including all vertebrates and a majority of the studied fungi/yeast, the site on antizyme mRNA where the shift occurs is UCC-UGA. The mechanism of the frameshift on this sequence likely involves nearly universal aspects of the eukaryotic translational machinery. Nevertheless, a mammalian antizyme frameshift cassette yields predominantly −2 frameshift in Saccharomyces cerevisiae, instead of the +1 in mammals. The recently identified endogenous S. cerevisiae antizyme mRNA has an atypical shift site: UGC-GCG-UGA. It is shown here that endogenous S. cerevisiae antizyme frameshifting is +1 rather than −2. We discuss how antizyme frameshifting in budding yeasts exploits peculiarities of their tRNA balance, and relate this to prior studies on Ty frameshifting.